DETERMINING LOWER-SECONDARY STUDENTS’ STEM MOTIVATION: A PROFILE FROM TURKEY - Dönmez, İsmail; Idin, S.; Gürbüz, S. (Scientia Socialis Ltd, 2022)
The ongoing motivation of students toward the fields of science, technology, engineering, and mathematics (STEM) is a process related to their orientation toward those fields and their active participation in related activities. This study aimed to examine the ongoing STEM motivations of lower-secondary school students in a sample from Turkey according to demographic variables. In this study, in which 1926 students from 12 provinces participated, the students’ STEM motivations were compared according to the variables of gender, place of residence, grade level, school type, “mothers’ and fathers’ education level, and family income level. T-tests and ANOVA testing were used in the analysis process via SPSS package program. As a result, male students’ STEM motivations were found to be at higher levels than those of female students. The STEM motivations of gifted students were found to be higher than those of students studying in religiously oriented education institutions. The results also revealed that STEM motivation is directly proportional to the education level of the parents. The results obtained in this study, reflecting the general profile of STEM motivation among students in Turkey, may guide education policy makers, program developers, teachers, prospective teachers, and researchers on STEM education. © 2022, Scientia Socialis Ltd. All rights reserved.
Keywords: lower-secondary school students; quantitative research; STEM; STEM motivation